https UJI EFEKTIVITASLIMBAHKULITBAWANGMERAH(ALLIUMCEPAL.)SEBAGAI PESTISIDANABATITERHADAPHAMAPADATANAMANTOMAT (SOLANUMLYCOPERSICUM): pestisida limbah kulit bawang merah - irfan, zahrulirfan; Haerudin, Haerudin; Dwi Rahayu Susanti, Dwi Rahayu Susanti (Fakultas Teknik Universitas Hamzanwadi, 2025)
The research method employed a completely randomized design with 4 treatments: control (P0), botanical pesticide concentrations of 10% (P1), 20% (P2), and 30% (P3). Pest population observations were conducted for 7 days post-application, identifying pest species including aphids (Aphis gossypii), thrips (Thrips tabaci), whiteflies, and armyworms. Data were analyzed using Shapiro-Wilk normality test, Levene's homogeneity test, and one-way ANOVA. Normality test results showed normally distributed data (sig. 0.196 > 0.05), homogeneity test indicated homogeneous variance (sig. 0.746 > 0.05), and ANOVA showed highly significant differences between treatments (F = 89.741; sig. 0.000 < 0.05). Treatment P3 demonstrated the highest effectiveness with an average pest population of 6.7 individuals (7.7% infestation), followed by P2 with 7.7 individuals (10.2%), P1 with 9.4 individuals (13.8%), and control with 12.7 individuals (17.6%). The coefficient of determination (R²) of 83.8% indicated that botanical pesticide treatments explained most of the variation in pest populations. This study proved that shallot peel-based botanical pesticide effectively controls pest populations with increasing effectiveness corresponding to higher concentrations, and possesses broad-spectrum control against various pest species.